A new species of Formicomotes Sevastianov (Acari: Heterostigmata: Dolichocybidae) associated with termites (Isoptera: Termitidae) from Brazil, with redescription of Formicomotes octipes Sevastianov, 1980 - Khaustov, Alexander A.; Frolov, Andrey V. (Zootaxa, 2018)
The new species Formicomotes brasiliensis sp. nov. (Acari: Heterostigmata: Dolichocybidae), phoretic on the termite genus Nasutitermes Dudley (Insecta: Isoptera) from Brazil, is described. The genus Formicomotes Sevastianov, 1980 is recorded from the Neotropical region for the first time. Formicomotes octipes Sevastianov, 1980 is redescribed based on type material collected on the ant species Lasius fuliginosus and new specimens from Crimea collected from forest litter.